Fabrication of bioactive conduits containing the fibroblast growth factor 1 and neural stem cells for peripheral nerve regeneration across a 15 mm critical gap - Ni, Hsiao-Chiang; Tseng, Ting-Chen; Chen, Jeng-Rung; Hsu, Shan-hui; Chiu, Ing-Ming (Biofabrication, 2013)
Nerve conduits are often used in combination with bioactive molecules and stem cells to enhance peripheral nerve regeneration. In this study, the acidic fibroblast growth factor 1 (FGF1) was immobilized onto the microporous micropatterned poly (D, L-lactic acid) (PLA) nerve conduits after open air plasma treatment. PLA substrates grafted with chitosan in the presence of a small amount of gold nanoparticles (nano Au) showed a protective effect on the activity of the immobilized FGF1 in vitro. Different conduits were tested for their ability to bridge a 15 mm critical gap defect in a rat sciatic nerve injury model. Axon regeneration and functional recovery were evaluated by histology, walking track analysis and electrophysiology. Among different conduits, PLA conduits grafted with chitosan-nano Au and the FGF1 after plasma activation had the greatest regeneration capacity and functional recovery in the experimental animals. When the above conduit was seeded with aligned neural stem cells, the efficacy was further enhanced and it approached that of the autograft group. This work suggested that microporous micropatterned nerve conduits containing bioactive growth factors may be successfully fabricated by micropatterning techniques, open plasma activation, and immobilization, which, combined with aligned stem cells, may synergistically contribute to the regeneration of the severely damaged peripheral nerve.